The effectiveness of dance therapy on pain in patients with venous insufficiency - Esra DOGRU HUZMELI; Iyad FANSA; Irem HUZMELI; Seyda Ciler SOYLEMEZ; Ayse KARAKAYA; Tugce ERKOVAN; Yonca ELCI (Editura Universităţii din Oradea, 2016)
Chronic venous insufficiency (CVI) is a condition that occurs when the venous wall and/or valves in the leg veins are not working effectively, making it difficult for blood to return to the heart from the legs. Exercise is a conservative treatment option which gives a potential of health benefits and also improves healing outcomes for people with venous leg ulcers. Dance therapy is an effective method for various disease. This study aimed to figure out the effects of dance therapy on pain of CVI patients. 40 patients were found to be available for this study and assigned to either the control group or the therapy group. Patients in control group received only medical treatment. Patients in dance therapy group received dance therapy in addition to medical treatment. 20 Patients in the dance therapy group had 3 times a week, for 5 weeks, totally 15 sessions of therapy, at Mustafa Kemal University Hospital. No differences between groups were observed in the pain (p>0.05). There was significantly difference in therapy group between pre and post-treatment results of rest and activity of VAS but in control group only activity score was significant (p<0.05). We found that dance therapy has positive effects on pain.